Perceptions of women about the experience of labor and delivery - Andressa Suelly Saturnino de Oliveira; Dafne Paiva Rodrigues; Maria Vilaní Cavalcante Guedes; Gilvan Ferreira Felipe (Rev Rene)
The perceptions about childbirth and how it is experienced are unique. This way, each woman should receive differentiated care. This research aimed at learning about the perception of mothers regarding their experience of labor and delivery. This exploratory descriptive and qualitative study was performed in a public secondary-level hospital in Fortaleza — Ceará, with fourteen mothers who were in the Rooming-in. Data were collected in August and September 2009, through interviews. The statements were organized according to the Content Analysis technique. The descriptions of labor and delivery have emphasized the overcoming of pain relief and happiness in being able to have the child in her arms, but the sensation of pain was presented as a criterion to classify the moment as negative, although necessary at birth. It is concluded that the experience of labor should be taken into consideration, as it brings impact to the participation of women in childbirth.